A Saturday's Trip to Epistemology - Larisa Segida (Canadian Society for Studies in Education, 2009)
This article examines a travailing search for a researcher's epistemological stance, which is essential for grounding any theorist in the domain of education. The author immerses the reader in an imaginary and cognitive journey in the labyrinths of epistemology and investigates some prominent paradigms, namely, postpositivism, social constructivism, critical theory, pragmatism, postmodernism, and poststructuralism. The work, with its combination of literary and scholarly features, demonstrates an unconventional approach to academic writing and emphasizes the importance of writing and its unique style in research. Writing as a method of knowing (Richardson, 2000) and an emergent methodology (Josephs, 2008) externalizes the individuality of the researcher and becomes an integral part of research methodology as a whole.